Electroluminescence as pre-breakdown phenomenon in polymers used for underground cable insulation - Mat Tajudin N.; Mohd Ariffin A. (2023)
The existence of space charge within a dielectric material can perturb the overall field of an electrically stressed polymer; causing long term degradation to the polymeric insulation. As a result of this, there has been increasing emphasis in understanding the behaviour of space charge in polymeric materials, together with the injection mechanisms responsible for its existence. One of the ways to investigate the role of space charge is by examining the energy dissipation of these charges. This dissipation process is associated with the emission of visible photon, known as electroluminescence (EL). The paper attempts to outline some of the developments in modelling of EL under uniform alternating field that may assist to assess the performance of insulating materials used in underground power cables. 2010 IEEE.